A rapid ultra high performance liquid chromatography–tandem mass spectrometry method for the quantification of daidzein, its valine carbamate prodrug, and glucuronide in rat plasma samples: Comparison of the pharmacokinetic behavior of daidzine valine carbamate prodrugs. Issue 19 (16th August 2021) - Li, Yingchao; Lu, Farong; Zhang, Yawei; Liu, Xiaoyu; Lin, Longyi; Jiang, Qikun; Zhang, Tianhong
Abstract: Two valine carbamate prodrugs of daidzein were designed to improve its bioavailability. To compare the pharmacokinetic behavior of these prodrugs with different protected phenolic hydroxyl groups of daidzein, a rapid and sensitive method for simultaneous quantification of daidzein, its valine carbamate prodrug, and daidzein‐7‐ O ‐glucuronide in rat plasma was developed and validated in this study. The samples were processed using a fast one‐step protein precipitation method with methanol added to 50 μL of plasma and were analyzed by ultra‐high performance liquid chromatography with tandem mass spectrometry. To improve the selectivity, peak shape, and peak elution, several key factors, especially stationary phase and the composition of the mobile phase, were tested, and the analysis was performed using the Kinetex ® C18 column (100 × 2.1 mm, 2.6 μm) within only 2.6 min under optimal conditions. The established method exhibited good linearity over the concentration range of 2.0–1000 ng/mL for daidzein, and 8.0–4000 ng/mL for the prodrug and daidzein‐7‐ O ‐glucuronide. The accuracy of the quality control samples was between 95.5 and 110.2% with satisfactory intra‐ and interday precision (relative standard deviation values < 10.85%), respectively. This sensitive, rapid, low‐cost, and high‐throughput method was successfully applied to compare the pharmacokinetic behavior of different daidzein carbamate prodrugs.